Robust Bayesian analysis of animal networks subject to biases in sampling intensity and censoring - Sosa, Sebastian; McElreath, Mary B.; Redhead, Daniel; Ross, Cody T. (Methods in ecology and evolution, 2025)
Data collection biases are a persistent issue for studies of social networks. This issue has been particularly important in animal social network analysis (ASNA), where data are often unevenly sampled and such biases may potentially lead to incorrect inferences about animal social behaviour. Here, we address the issue by developing a Bayesian model, which not only estimates network structure but also explicitly accounts for sampling and censoring biases. Using a set of simulation experiments designed to reflect various sampling and observational biases encountered in real‐world scenarios, we systematically validate our model and evaluate its performance relative to other common ASNA methodologies. By accounting for differences in node‐level censoring (i.e. individual variation in undetected ties), our model permits the recovery of true latent social connections, even under a wide range of conditions where some key individuals are intermittently unobserved. Our model outperformed all other existing approaches and accurately captured network structure, as well as individual‐level and dyad‐level effects. Antithetically, permutation‐based and simple linear regression approaches performed the worst across many conditions. These results highlight the advantages of generative network models for ASNA, as they offer greater flexibility, robustness and adaptability to real‐world data complexities. Our findings underscore the importance of generative models that jointly estimate network structure and measurement biases typical in empirical studies of animal social behaviour.